Vascular Signaling in Allogenic Solid Organ Transplantation – The Role of Endothelial Cells - Kummer, Laura; Zaradzki, Marcin; Vijayan, Vijith; Arif, Rawa; Weigand, Markus A.; Immenschuh, Stephan; Wagner, Andreas H.; Larmann, Jan (Frontiers in Physiology, 2020)
Graft rejection remains the major obstacle after vascularized solid organ transplantation. Endothelial cells, which form the interface between transplanted graft and hosts immunity, are the first target for host immune cells. During acute cellular rejection endothelial cells are directly attacked by HLA I and II recognizing NK cells, macrophages and T cells and activation of the complement system leads to endothelial cell lysis. Established immunosuppressive therapy provides effective treatment options, whereas treatment of chronic rejection of solid organs remains challenging. Chronic rejection is mainly based on production of donor-specific antibodies which induce endothelial cell activation - a condition which phenotypically resembles chronic inflammation. Activated endothelial cells produce chemokines and expression of adhesion molecules increases. Due to this pro-inflammatory microenvironment, leukocytes will be recruited and transmigrate from the blood stream across the endothelial monolayer into the vessel wall. This mononuclear infiltrate is a hallmark of transplant vasculopathy. Furthermore, expression profiles of different cytokines serve as clinical markers for patients’ outcome. Besides their effects on immune cells, activated endothelial cells root for migration and proliferation of vascular smooth muscle cells. In turn, muscle cell recruitment leads to a narrowing of the vessel lumen followed by reduction in organ perfusion and eventually results in tissue injury. Activation of endothelial cells comprises antibody ligation to the surface of endothelial cells. Subsequently intracellular signaling pathways are initiated. Those signaling cascades might serve as targets to prevent or treat adverse effects in antibody-activated endothelial cells. Preventive or therapeutic strategies for chronic rejection can be investigated in sophisticated mouse models of transplant vasculopathy mimicking interactions between immune cells and endothelium.